2021
DOI: 10.1101/2021.10.04.463077
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CNN MouseNet: A biologically constrained convolutional neural network model for mouse visual cortex

Abstract: Convolutional neural networks trained on object recognition derive inspiration from the neural architecture of the visual system in primates, and have been used as models of the feedforward computation performed in the primate ventral stream. In contrast to the deep hierarchical organization of primates, the visual system of the mouse has a shallower arrangement. Since mice and primates are both capable of visually guided behavior, this raises questions about the role of architecture in neural computation. In … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Finally, we found that lowering the resolution of the inputs during model training led to improved correspondence with the neural responses across model architectures, including current deep CNNs (VGG16 and ResNet-18) used in prior comparisons to mouse visual data [26,211,47,43]. Thus, strong constraints even at the level of input transformations improve model correspondence to the mouse visual system, although there remains a small gap between these models and the inter-animal consistency ceiling.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Finally, we found that lowering the resolution of the inputs during model training led to improved correspondence with the neural responses across model architectures, including current deep CNNs (VGG16 and ResNet-18) used in prior comparisons to mouse visual data [26,211,47,43]. Thus, strong constraints even at the level of input transformations improve model correspondence to the mouse visual system, although there remains a small gap between these models and the inter-animal consistency ceiling.…”
Section: Introductionmentioning
confidence: 89%
“…We found that the neural response predictions of a standard deep CNN model (VGG16), used in prior comparisons to mouse visual areas [26,211,47], were quite far from the inter-animal consistency (56.27%). Retraining this model with images of resolution closer to the visual acuity of mice (64×64 pixels) improved the model's neural predictivity, reaching 67.7% of the inter-animal consistency.…”
Section: Architecture: Shallow Architectures Better Predict Mouse Vis...mentioning
confidence: 95%
See 1 more Smart Citation
“…In summary, only novel combinations of architecture, task and mapping will help to explain the highly reliable neural variance we’ve yet to explain in our current survey. Already this recombination is under way: Shi et al [97] have created a custom CNN designed specifically to match (processing stage by processing stage) the anatomy of rodent visual cortex, while Nayebi et al [88] have combined the power of self-supervised learning with smaller, shallower architectures to more fully account for the ethological realities of rodent behavior and the differences in computational bandwidth that shape and constrain their visual systems. More work of this variety will be necessary to more fully model the rich diversity and fiendish complexity of biological brains at scale – even the very smallest ones.…”
Section: Discussionmentioning
confidence: 99%
“…Best practice for this interfacing remains unclear in the absence of more comprehensive empirical controls. The use of custom models (as in Nayebi et al [88] and Shi et al [97]), on the other hand, does not carry with it the same concerns as the use of pretrained models, and seems a promising path forward for probing the effects of input manipulations directly.…”
Section: Does Our Neural Regression Methods Work?mentioning
confidence: 99%